Green finance: Regulation and instruments - Vesna Martin (Journal of Central Banking Theory and Practice, 2023)
Green finance is the basis for the development of sustain-able financing of environmental projects with the aim of respectingenvironmental and social aspects in making investment decisions.The development of green finance enables a green transition towardseconomic growth that will be sustainable in the long run because itis based on the principles of preserving the environment and reduc-ing the risk of climate change. This creates a basis for preservingmacroeconomic stability based on the development of new alterna-tive sources of financing. The aim of this paper is to present greenfinance, with special reference to Serbia. The paper covers the regula-tion of green finance, but also the analysis of green finance instru-ments in terms of types and features and their development.
Keywords: E44; E58; O44; Q58; 330; reen finance; sustainability objectives; environmentregulation; climate protection